國中課室素養導向標準本位評量的設計與應用：以英語科閱讀為例 Development and Implementation of a Standardized Junior High School Classroom Literacy Assessment: English Reading Comprehension as an Example - 曾芬蘭 Fen-Lan Tseng; 鍾長宏 Chang-Hung Chung; 陳世玉 Shih-Yu Chen; 張銘秋 Ming-Chiu Chang (National Taiwan Normal University, 2018)
近年來愈來愈多先進國家持續推動以標準為本位的教育評量改革，我國自2014年起推動十二年國民基本教育，並同時實施以標準參照計分的國中教育會考作為國中畢業生學力監控機制。在高風險考試之外，本研究以英語科為例，聚焦於探討如何在國中課室設計素養導向標準本位評量工具，並透過實際參與標準本位評量試辦的學生與教師的經驗及意見，分析情境式素養導向的標準本位課室評量如何提振學生興趣，促進英語學習。研究結果如下：一、依據學生作答感受問卷調查結果，在使用經多次命修審與預試的評量作業的情境之下，近七成的學生認為較傳統選擇題或填充題更容易發揮、更具有挑戰性、也較活潑有趣；六成左右學生的作答意願較高、心情比較愉快，也認為比較容易得分；二、依據試辦教師的回饋可知， 多樣化題型搭配標準參照評等及彈性的作答方式，可激發學生多元能力表現，並從評量的過程與結果，讓學生明瞭自身學習狀況，也可促進教師專業知能的成長；三、情境式試題設計可引導學生從評量中學習將所理解的訊息，應用於仿真的新情境以解決問題，藉此幫助學生體會英語閱讀的實用性與實質意義。若能在國中英語科的課室中，實施類似本研究所提出之素養導向標準本位課室的多元評量，可「善誘學生學習動機與熱情」，促進自發學習，增進英語學習成效，有利培養學生成為十二年國教核心素養所強調的「終身學習者」。 The number of developed countries that have initiated standardized education reform has increased over the last two decades. At the same time that the ministry of education in Taiwan implemented the 12-year basic education policy, they announced regulations for implementing a standardized comprehensive assessment program to monitor the achievement of junior high school students. This study investigated the implementation of a standardized classroom literacy assessment for English classes in junior high schools as an alternative formative-assessment option. In this study, we developed a standardized seventh-grade English (L2) reading-literacy sample task and collected student work and feedback from participating teachers and students. The reading task was scenario-based and required that students search for missing pets. The study results are as follows: (1) Nearly 70% of the participating students agreed that the high-quality scenario-based reading task was more interesting, fulfilling, and challenging than traditional tests. (2) The use of a standardized approach for assessing English reading literacy can enhance the learning motivation of students because it not only grants students the freedom to respond diversely (e.g. to demonstrate understanding by drawing pictures or using Chinese, their first language), but also helps students to learn English more effectively through post-assessment feedback. (3) The scenario-based reading task is an assessment that is useful for learning because it encourages students to apply knowledge to real-life problems, clarifying for students the meaning and value of learning English. Therefore, if a standardized literacy assessment is implemented in Taiwan's junior high school English classrooms, then students can gain motivation not only for learning English but eventually for lifelong learning, which is the ultimate goal of Taiwan's 12-year basic education curriculum reform.